Identification of Streptomyces coelicolor M145 genomic region involved in biosynthesis of teichulosonic acid-cell wall glycopolymer - Ostash, Bohdan; Shashkov, Alexander; Streshinskaya, Galina; Tul'skaya, Elena; Baryshnikova, Lidiya; Dmitrenok, Andrey; Dacyuk, Yuriy; Fedorenko, Victor (Folia microbiologica, 2014)
The cell wall of the model actinomycete Streptomyces coelicolor M145 has recently been shown to contain the novel glycopolymer teichulosonic acid. The major building block of this polymer is 2-keto-3-deoxy-D-glycero-D-galacto-nononic acid (Kdn), suggesting initial clues about the genetic control of biosynthesis of this cell wall component. Here, through genome mining and gene knockouts, we demonstrate that the sco4879-sco4882 genomic region of S. coelicolor M145 is necessary for biosynthesis of teichulosonic acid. Specifically, mutants carrying individual knockouts of sco4879, sco4880 and sco4881 genes do not produce Kdn-containing glycopolymer and instead accumulate the minor cell wall component poly(diglycosyl 1-phosphate). Our studies provide evidence that this region is at least partly responsible for biosynthesis of Kdn, whereas flanking genes might control the other steps of teichulosonic acid formation.
Keywords: DNA bakterií; buněčná stěna; klonování DNA; Streptomyces coelicolor; kyseliny cukerné; Polysaccharides, Bacterial; Magnetic Resonance Spectroscopy; bakteriální polysacharidy; Cell Wall; Cloning, Molecular; DNA, Bacterial; Mutagenesis, Insertional; data mining; Sugar Acids; inzerční mutageneze; magnetická rezonanční spektroskopie; Data Mining